Patient‐controlled tissue collection for genetic testing after early pregnancy loss: A pilot study. (31st January 2018) - Kucherov, Alexander; Atrio, Jessica; Williams, Zev
Abstract: Objective: To determine how frequently and effectively products of conception can be obtained among women pursuing medical management of early pregnancy loss. Methods: This pilot study was conducted to assess products of conception recovery outcomes for participants opting for medical management compared with women opting for surgical aspiration A tissue‐collection kit was provided to women opting for medical management. Outcome measures included successful collection of products of conception, quantity and integrity of DNA, and participant satisfaction with the process. Results: Tissue was collected from 19 of 22 participants in the medical management group (84%) and 39 participants (100%) in the surgical management group ( P = .02). DNA yield and integrity were similar among both groups ( P = .03 and P = .003, respectively). Participants in the medical group reported a high comfort level with the kit and the process of tissue collection. Conclusions: Medical management of a missed abortion followed by patient‐controlled collection of products of conception for subsequent cytogenetic analysis is well tolerated and highly effective. This methodology may reduce the need for surgical management, empower women to have more agency in their medical decisions, and increase access to genetic testing. Abstract : What is already known about this topic? In instances when cytogenetic testing of products of conception is clinically indicated, surgical aspiration is typically recommended. Medical management is often discouraged because of a long‐standing assumption that tissue may not be successfully obtained for subsequent cytogenetic testing. Reliable products of conception collection with medical management of a missed abortion would give women greater choice in the management of their losses and the option to avoid surgical management. What does this study add? This study validates a patient‐controlled tissue‐collection approach that has the potential to expand access to care and improve patient‐centered outcomes. Offering women more options for management of an early pregnancy loss could significantly impact a clinician's ability to provide optimal preconception counseling and management guidance for future pregnancies.